Leadership Behind Closed Doors: The Role of Husbands in Supporting or Hindering Women’s Professional Advancement in Uzbekistan - Dilafruz Kuchkorova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This study examines the impact that husbands have on the careers of women in Uzbekistan. It focuses on the question of whether husbands function as supporters, detractors, or are indifferent to their wives' professional advancement by integrating gender role theory alongside social support theory. Based on a survey of 109 married women from different urban and rural areas of Uzbekistan, especially Khorezm and Tashkent, we assess the influence that emotional support, household chore sharing, and prevailing societal norms regarding femininity and masculinity have on women’s employment decisions and career progression. These findings are relevant in guiding policy development with regard to gender issues, particularly about family assistance programs and stimulating female participation in the labor force.